The influence of fatherlessness on resilience in children aged 5–6 years in Surabaya. - Rizka Anugrah Syakira; Wulan Patria Saroinsong; Novita Widiyaningrum (Journal of Art and Creativity in Early Childhood Education, 2025)
This study aims to find out the influence of fatherlessness on children's resilience in Surabaya City. The background of this research is based on the increasing divorce rate, and research findings indicate that the minimal involvement of fathers in children's lives has the potential to have psychological impacts on children, which can subsequently affect their ability to build resilience. This research uses quantitative research methods with data collected thru a questionnaire survey. The sample in this study consisted of 5-6 year old children in the city of Surabaya, with 155 children serving as the research sample. The analysis tests consisted of validity tests, reliability tests, and simple regression tests. The data was then analyzed using SPSS 25 software for hypothesis testing. Based on the research findings, it is concluded that there is a significant influence of the fatherless variable on the resilience of 5-6 year old children in the city of Surabaya. This is indicated by the Sig. value from the Regression test, which is 0.000 < 0.05. This means Ha is accepted and Ho is rejected. The higher the level of fatherlessness in children, the lower their level of resilience.